Optimal design of series production lines with unreliable machines and finite buffers - Nourelfath, Mustapha; Nahas, Nabil; Ait-Kadi, Daoud (Journal of quality in maintenance engineering, 2005)
Purpose - The purpose of this paper is to formulate a new problem of the optimal design of a series manufacturing production line system, and to develop an efficient heuristic approach to solve it. The optimal design objective is to maximize the efficiency subject to a total cost constraint.Design methodology approach - To estimate series production line efficiency, an analytical decomposition-type approximation is used. The optimal design problem is formulated as one of combinatorial optimization where the decision variables are buffers and types of machines. This problem is solved by developing and demonstrating a problem-specific ant system algorithm. Numerical examples illustrate the effectiveness of the algorithm.Findings - It has been found that this algorithm can always find near-optimal or optimal solutions quickly. The approach developed in this paper for manufacturing lines can be adapted for power systems and telecommunication systems.Originality value - The paper presents a new approach for the optimal design of buffered series production lines. This optimization approach aims at selecting both the machines and the levels of buffers. The paper also develops an efficient solution approach based on the ant system meta-heuristic.